Tokoh-Tokoh Kuat Lokal, Konversi Modal, dan Kemunculan Dinasti Politik di Indonesia Pasca-Desentralisasi: Studi Kasus Aras Tammauni di Mamuju Tengah - Pramita Khanifatul Khusna (Journal of Legal, Political, and Humanistic Inquiry, 2025)
This study examines how local strongmen in post-decentralization Indonesia convert economic, social, and symbolic capital into enduring political dominance, using Aras Tammauni in Central Mamuju as a case study. Drawing on qualitative fieldwork including interviews, observations, and document analysis the research explores the mechanisms of capital conversion that underpin the consolidation of local power and the reproduction of political dynasties. Findings reveal that Tammauni’s authority derives from the strategic transformation of economic resources into patronage networks, reinforced by kinship ties, customary legitimacy, and symbolic recognition. These interrelated forms of capital enable the institutionalization of dynastic rule through control of party structures, bureaucratic appointments, and public resource distribution. The study also situates Central Mamuju within the national trend of rising dynastic candidacies, showing that nearly one-fifth of candidates in Indonesia’s 2024 local elections are dynasty-affiliated. The analysis concludes that decentralization, rather than democratizing local politics, has facilitated elite entrenchment and capital-based domination, necessitating stronger regulatory and civic mechanisms to restore accountability and inclusiveness in regional governance.